Low Cost Data Acquisition and Control Systems for Personal Computers - Jayananda, M.K.; Sonnadara, D.U.J. (My University, 1998)
A detailed study of building low cost data acquisition and equipment control systems for personal computers containing analog-to-digital (ADC) and digital-to analog (DAC) converters is carried out. Two types of boards (based on AD7569 and ADC0816) were successfully constructed and implemented for the standard 8-bit ISA bus. These boards can be constructed under SLR 7,500 /- each and give much more flexibility than the expensive data acquisition cards that are sold in the market. By writing the control system software, the same card can be used for various purposes.
Keywords: Instrumentation